2018
DOI: 10.1111/jvim.15132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunosuppressive agents on the hemostatic system in normal dogs

Abstract: BackgroundIn dogs, the effects of immunosuppressive medications on hemostasis are not well known.Hypothesis/ObjectivesThe objective was to determine the effects of immunosuppressive medications on primary and secondary hemostasis. Our hypothesis was that cyclosporine and prednisone would increase markers of hypercoagulability and thromboxane synthesis, while azathioprine, mycophenolate mofetil, and leflunomide would have minimal effects on hemostasis.AnimalsEight healthy dogs.MethodsA randomized, cross‐over st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 39 publications
4
8
1
Order By: Relevance
“…As expected, thromboxane concentrations in both the aspirin and prednisone groups were significantly decreased compared to the placebo group. The results of our study contrast with results of a prior study in healthy dogs administered the same prednisone dose and using the same assay to measure 11-dTXB 2 (31). In that study, an 80% increase in thromboxane concentration was noted after administration of the same prednisone dosage for 7 days to healthy dogs, although the increase was not consistent among dogs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As expected, thromboxane concentrations in both the aspirin and prednisone groups were significantly decreased compared to the placebo group. The results of our study contrast with results of a prior study in healthy dogs administered the same prednisone dose and using the same assay to measure 11-dTXB 2 (31). In that study, an 80% increase in thromboxane concentration was noted after administration of the same prednisone dosage for 7 days to healthy dogs, although the increase was not consistent among dogs.…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies, there have been contrasting results regarding platelet reactivity during the administration of immunosuppressive doses of prednisone. Similar to our study, Thomason et al did not detect a significant difference in platelet function following administration of immunosuppressive doses of prednisone to healthy dogs (31). In contrast, despite using the same agonist to initiate platelet aggregation, Romao et al demonstrated increased platelet aggregation in dogs treated with an immunosuppressive, but not an anti-inflammatory, dose of prednisone (32).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding is congruent with a recent study, which investigated the platelet aggregatory effect of leflunomide in 8 healthy dogs with LTA after 7 days treatment with leflunomide 20 With tocilizumab, the initial screening demonstrated an effect on ADP-, TRAPand collagen-induced platelet aggregation with 96-well LTA, but no effect on flow cytometric platelet aggregation. A previous study demonstrated no effect on TRAPinduced platelet aggregation in spiked samples from five healthy individuals 23 .…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, fewer studies have been performed in dogs, with variable results, that have assessed the effects of exogenous glucocorticoids on platelet reactivity. One study did not detect a significant difference in platelet function after administration of prednisone (2 mg/kg PO q24h) to healthy dogs 24 . In contrast, another study identified increased platelet aggregation in dogs treated with prednisone at a dosage of 2 mg/kg PO q12h, but not at a prednisone dosage of 1 mg/kg PO q12h 25 .…”
Section: Discussionmentioning
confidence: 97%